Preparation method of calcium lactate modified corn straw biomass charcoal
Through the preparation method of calcium lactate modified corn straw biomass char, the problem of general and high cost of TeA adsorbent in the prior art is solved, and the effect of significantly improving TeA adsorption effect and reducing costs is achieved.
Patent Information
- Application Number
- CN202411839665.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, there are few adsorbents for removing mycotoxin tetrasporic ketoacid (TeA), and are mostly biological methods for inactivated cells as adsorbents, with general effects and high costs.
The preparation method of calcium lactate modified corn stalk biomass charcoal was prepared by uniformly mixing corn stalk powder and calcium lactate in proportion and grinding them thoroughly, and reacting in a tube furnace to react, calcium lactate modified corn stalk biochar with significant adsorption effect.
The adsorption effect of this adsorbent is significant, with an adsorption amount of more than three times that of inactivated cells. The adsorption amount of TeA in apple juice is also greater than that of inactivated cells, and has almost no effect on the key nutrients in apple juice.
Smart Images

Figure CN119869461A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent preparation, and in particular to a method for preparing calcium lactate modified corn stalk biochar. Background Art
[0002] Alternaria fungi can easily infect fruits rich in nutrients, such as apples and apple products. Among the series of Alternaria toxins it produces, which are mutagenic, carcinogenic, teratogenic, and lethal, Tenuazonic acid (TeA) is the most toxic and has been listed as a toxic compound by the U.S. Food and Drug Administration.
[0003] The removal mechanism of mycotoxins mainly includes adsorption and degradation. Adsorption treatment is to remove mycotoxins by applying adsorbents with large specific surface area. Degradation treatment is to remove mycotoxins by destroying the chemical structure of mycotoxins, especially the toxic groups in the chemical structure, through certain strategies. Chemical, biological and physical methods are the main strategies for adsorbing and degrading mycotoxins. Although chemical methods have certain effects, they will cause certain damage to nutrients in actual applications. Biological methods mainly destroy and modify mycotoxins through microorganisms or their extracts to achieve the purpose of reducing or eliminating toxins, but this method is difficult to operate at the current research level, the cost is high, and it has not yet reached the industrial stage. Among physical methods, the use of adsorbents for detoxification is a relatively mature method for removing mycotoxins that has been widely concerned and valued in recent years.
[0004] In recent years, the rapid development of agriculture has led to the disposal of a large amount of agricultural and forestry waste (such as corn stalks, cotton stalks and jujube branches). Through chemical modification and high-temperature pyrolysis, a large amount of agricultural and forestry waste in Xinjiang has been converted into biochar for the removal of mycotoxins in food. This not only solves the problem of difficult waste treatment, but also provides environmentally friendly biochar materials. At present, there are few studies on adsorbents for TeA adsorption, and most of them are biological methods using inactivated cells as adsorbents, with general adsorption effects and relatively high costs. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing calcium lactate modified corn straw biochar to solve the problems raised in the background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing calcium lactate modified corn straw biochar comprises the following steps: step one is preparation of biomass powder, which comprises washing and drying corn straw and then crushing and sieving to obtain uniform corn straw biomass powder; step two is preparation of calcium lactate modified corn straw biochar, which comprises uniformly mixing the obtained corn straw biomass powder and calcium lactate according to a proportion, then fully grinding and placing in a tubular furnace for reaction to obtain calcium lactate modified corn straw biochar.
[0007] On the basis of the above technical solution, the present invention also provides the following optional technical solution: In an optional scheme: in the step 1, the corn stalks are cleaned and cut into 10 cm segments, dried at 105° C. overnight, and crushed and passed through a 60-mesh sieve.
[0008] In an optional embodiment, the ratio of calcium lactate to corn straw powder is 1:20, 1:4, 1:2, 1:1 or 2:1.
[0009] In an optional scheme: in the step 2, the tubular furnace is filled with N2 gas, heated to 600-1000℃ at a heating rate of 5℃ / min, and maintained at 600-1000℃ for 1 hour, and finally cooled to room temperature, the prepared biochar is taken out, washed twice with distilled water, and placed in a 105℃ oven for 12 hours to obtain calcium lactate modified corn straw biochar.
[0010] In an alternative scheme: the tube furnace is filled with N2 gas, heated to 800℃ at a heating rate of 5℃ / min, and maintained at 800℃ for 1 h.
[0011] The role of the calcium lactate-modified corn straw biochar prepared by the above-mentioned method for preparing calcium lactate-modified corn straw biochar in the adsorption of TeA.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: The calcium lactate modified corn straw biochar prepared by the present invention has a significant adsorption effect, which is more than 3 times the adsorption amount of existing inactivated cells in TeA solution; the adsorption amount in apple juice is also greater than the adsorption amount of inactivated cells adsorbing TeA in citrus juice, and the adsorption process has almost no effect on the content of key nutrients (malic acid and sugars) in apple juice; BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a bar chart showing the removal efficiency of TeA by cotton straw charcoal, corn straw charcoal and jujube branch charcoal.
[0014] Figure 2TeA removal efficiency of (a) corn straw biochar, CLBC0.05, CLBC0.25, CLBC0.5, CLBC1, CLBC2, (b) CLBC0.25, CLBC0.25-800, CLBC0.25-1000, SEM images of (c) corn straw biochar, (d) CLBC0.25, (e) CLBC0.25-800 and the enlarged image of the position circled in the red frame, (f) N2 adsorption-desorption isotherms of corn straw biochar, CLBC0.05, CLBC0.25, CLBC0.5, CLBC1, CLBC2 and (g) CLBC0.25, CLBC0.25-800, CLBC0.25-1000.
[0015] Figure 3 SEM images of (a) and (b) CLBC0.05, (c) and (d) CLBC0.25, (e) and (f) CLBC0.5, (g) and (h) CLBC1, (i) and (j) CLBC2.
[0016] Figure 4 SEM images of (a) and (b) CLBC0.25, (c) and (d) CLBC0.25-800, (e) and (f) CLBC0.25-1000.
[0017] Figure 5 It is the pore size distribution of CLBC0.25, CLBC0.25-800 and CLBC0.25-1000.
[0018] Figure 6 Effects of (a) and (b) adsorbent dosage, (c) and (d) initial TeA concentration, and (e) and (f) temperature on the adsorption capacity and removal efficiency of TeA by CLBC0.25-800.
[0019] Figure 7 (a) Pseudo-first-order, pseudo-second-order, and Elovich kinetic models for the adsorption of TeA by CLBC0.25-800; (b) intramolecular diffusion kinetic model and (c) Langmuir, Freundlich, and Temkin isotherm models; (initial concentration = 100 μg / L, adsorbent dosage = 3 g / L, temperature = 30°C).
[0020] Figure 8 (a) XRD spectra of corn straw biochar, CLBC0.25 and CLBC0.25-800; (b) FTIR spectra and (c) XPS overall pattern; XPS spectra of (d) C 1s, (e) O 1s and (f) Ca 2p of CLBC0.25-800.
[0021] Fig. 9 This is the XRD spectrum of CLBC0.25-1000.
[0022] Fig.10 Schematic diagram of sugar (fructose, glucose, sucrose, μg / 100g) and malic acid (μg / kg) content in experimental groups A, B, and C. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The various embodiments listed in the present invention are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any obvious modifications or changes made to the present invention do not depart from the spirit and scope of the present invention.
[0024] The present invention provides a preparation method and application of calcium lactate modified corn straw biomass charcoal that efficiently adsorbs TeA in water and apple juice. The adsorbent has a significant effect on adsorbing TeA and has no effect on the sugar and acid content in apple juice; 1. The preparation method of calcium lactate modified corn straw biochar comprises the following steps: Step 1. Preparation of biochar The agricultural and forestry waste (jujube branches, corn stalks, and cotton stalks) were washed with clean water, cut into 10 cm segments, dried at 105 °C overnight, crushed with a grinder, and passed through a 60-mesh sieve to obtain uniform biomass powder. 10.0 g of biomass powder was placed in a tubular furnace, heated to 600 °C at a heating rate of 5 °C / min under N2 gas protection, and maintained at 600 °C for 1 h. After cooling to room temperature, the prepared black powdered biochar was taken out, washed twice with distilled water, and placed in a 105 °C oven for 12 h to obtain jujube branch biochar, corn stalk biochar, and cotton stalk biochar.
[0025] Step 2. Preparation of calcium lactate-modified corn straw biochar The obtained corn straw powder and calcium lactate were uniformly mixed and fully ground according to the proportion, and placed in a tube furnace for reaction. The synthesis method in step 1 of the following steps was consistent; the ratios of calcium lactate to corn straw powder were 1:20, 1:4, 1:2, 1:1, and 2:1, respectively, and the calcium lactate-modified corn straw biochars were recorded as CLBC0.05, CLBC0.25, CLBC0.5, CLBC1, and CLBC2 according to the ratios of calcium lactate to corn straw powder.
[0026] Except that the pyrolysis temperature of CLBC0.25 was increased from 600 °C to 800 °C or 1000 °C, the rest of the experimental steps and conditions were carried out according to step 1, and the obtained biochars were recorded as CLBC0.25-800 and CLBC0.25-1000, respectively.
[0027] Adsorption properties of corn straw biochar modified with calcium lactate 1. Adsorption experiment Experimental conditions for the adsorption of TeA by jujube branch biochar, corn straw biochar, cotton straw biochar, CLBC0.05, CLBC0.25, CLBC0.5, CLBC1, and CLBC2: 1.0 g of biochar adsorbed 100 μg / L TeA standard solution for 3 h. Due to the strong adsorption capacity of CLBC0.25-800 and CLBC0.25-1000, the adsorption experimental conditions of CLBC0.25-800 and CLBC0.25-1000 were as follows: 0.1 g of CLBC0.25-800 and CLBC0.25-1000 biochar were weighed and placed in 100 μg / L TeA standard solution and shaken for 3 h.
[0028] Through the CLBC adsorption of TeA batch experiment, different amounts of TeA standard solutions were prepared in a series of 50 mL centrifuge tubes, and a certain amount of biochar was added to adsorb for a certain time in a constant temperature shaking incubator at 25 ℃, centrifuged at 10000 r / min for 5 min, and the supernatant was taken to determine the residual TeA concentration using UPLC-MS / MS detection method. The main factors affecting the adsorption effect were analyzed, including the initial concentration of TeA solution (10, 20, 50, 100, 200, 300, 400 μg / L), adsorption time (20, 40, 60, 80, 100, 120, 140, 160, 180 min), adsorbent dosage (0, 1, 3, 5, 10, 12, 20 mg / mL) and adsorption temperature (30, 40, 50 ℃).
[0029] In all the above experiments, the spiked solution without biochar was used as the blank control, and three replicates were set for each treatment.
[0030] 2. Calculate the fit ①The adsorption amount qt and adsorption rate are calculated by the following formula:
[0031]
[0032] Where: Initial toxin concentration, μg / mL; —Toxin concentration after adsorption equilibrium, μg / mL; —Concentration of toxin after adsorption at time t, μg / mL; —Volume of the experimental adsorption system, mL; —Mass of biochar added, g.
[0033] ②Adsorption thermodynamics study The adsorption isotherm model is used to describe the relationship between equilibrium adsorption amount and equilibrium concentration, and can provide a basis for the analysis of adsorption mechanism. The Langmuir isotherm model, the Freundlich isotherm model and the Temkin isotherm model are three commonly used adsorption isotherm models.
[0034] Langmuir Isotherm Model Freundlich Isotherm Model Temkin Isotherm Model Where: —Adsorption amount at equilibrium, μg / g; —Saturated adsorption capacity, μg / g; —Concentration of adsorbate at equilibrium, μg / mL; —Adsorption energy constant associated with Langmuir adsorption; —Freundlich adsorption constant; —Freundlich adsorption constant; — dimensionless constant; R—Universal gas constant 8.314 JK -1 mol -1 ; T—absolute temperature, K; b. K T —Isothermal adsorption characteristic constant.
[0035] The optimal amount of biochar was added to 10 mL of TeA solution with a concentration of 10, 20, 50, 100, 250, and 500 μg / L, and then placed at the optimal adsorption temperature for the optimal adsorption time. The control was a TeA solution without biochar. Each treatment was repeated for 2 groups. After the adsorption, the TeA concentration was measured and the equilibrium adsorption amount was calculated. The linear fitting of the three adsorption isotherm models and the calculation of related thermodynamic parameters were performed based on the experimental data.
[0036] The relevant thermodynamic indices were calculated using a well-fitting isothermal adsorption model. Thermodynamic studies determined the thermodynamic parameters, including the changes in standard enthalpy ΔH, standard entropy ΔS, and Gibbs free energy ΔG. ΔH and ΔS were calculated using the Van't Hoff equation:
[0037]
[0038] The calculation formula of Gibbs free energy ΔG is as follows: Where: —Equilibrium adsorption capacity, μg / g; —Equilibrium adsorption concentration, μg / mL; R—Universal gas constant 8.314 JK -1 mol -1 ; —thermodynamic equilibrium constant; T—absolute temperature, K.
[0039] ③Adsorption kinetics study Adsorption kinetics mainly studies the relationship between the amount of adsorbate adsorbed on the adsorbent and the adsorption time. Commonly used adsorption kinetic models include pseudo-first-order, pseudo-second-order and ion diffusion models. The expression is as follows: Pseudo-first-order reaction kinetic model:
[0040] Pseudo-second-order reaction kinetic model:
[0041] Ion internal diffusion model:
[0042] Elovich Model:
[0043] Where: —Equilibrium adsorption capacity, μg / g; —The amount of adsorption at any time t, μg / g; —Pseudo-first-order kinetic rate constant (min -1 ); —Pseudo-second-order kinetic rate constant (g / μg / min); —Ion diffusion rate constant (μg / g / min 0.5 ). The adsorption experiment was conducted at the optimal adsorbent dosage, the optimal initial TeA concentration, and the optimal adsorption temperature, and the relationship between the adsorption amount and time.
[0044] ④Evaluation of the effect of biochar on the adsorption of TeA in apple juice Apple juice without biochar and toxins and apple juice solution spiked with biochar were used as the control group. The malic acid, fructose, glucose, sucrose and other indicators in the spiked apples with biochar after adsorption were determined. The measurement was repeated 3 times for each group of samples to evaluate the adsorption effect and application value of biochar in apple juice.
[0045] Results and Discussion (1) Original and modified biochar adsorbents Since the use of different raw materials and modification methods will affect the removal efficiency of TeA by biochar, this study compared the removal efficiency of TeA by unmodified, calcium lactate-modified, and calcium lactate-modified biochars at different pyrolysis temperatures. In a N2 atmosphere, the biomass raw materials were directly pyrolyzed at 600°C to obtain jujube branch biochar, corn straw biochar, and cotton straw biochar without secondary modification. Figure 1 As shown in Figure 2, the adsorption experiment confirmed that among the three biochars, corn straw biochar had the best removal effect on TeA. Corn straw biochar has a strong adsorption capacity, which must be attributed to its inherent unique hollow tubular structure.
[0046] SEM image of corn straw biochar ( Figure 2 c) It can also be proved that the corn straw biochar maintained a smooth hollow tubular structure, and no impurity deposition was observed. To further enhance the adsorption capacity of corn straw biochar, food additive calcium lactate was selected as a non-toxic chemical activator to prepare cost-effective calcium-modified biochar.
[0047] The CLBCs with different mass ratios of calcium lactate to corn straw (1:20, 1:4, 1:2, 1:1, 2:1) were recorded as CLBC0.05, CLBC0.25, CLBC0.5, CLBC1 and CLBC2. The adsorption experiment showed that CLBC0.25 had the highest removal efficiency ( Figure 2 a).
[0048] Figure 3 The morphological characterization of calcium-modified biochar at different mass ratios is shown. It can be seen that as the proportion of calcium lactate gradually increases, the rougher the CLBC surface is, the more fragments accumulate in the tubular pores. Especially for CLBC1 and CLBC2, a large number of broken fragments seriously destroyed the inherent porous structure of corn stalks.
[0049] Combined with N2 adsorption-desorption isotherms and Figure 2 f and the data obtained from the N2 adsorption-desorption isotherms of CLBC0.05, CLBC0.25, CLBC0.5, CLBC1, and CLBC2 in Table 1 can further confirm that the best TeA removal efficiency of CLBC0.25 may be due to its largest specific surface area (SSA) of 132.7357 m2 g -1 and pore volume 0.064371 cm 3 g -1 .
[0050] In summary, CLBC0.25 can reasonably improve the distribution of porous structure without destroying the inherent pore structure of corn stalk ( Figure 2 d), the optimal mass ratio of chemical activator to corn straw is 1:4.
[0051] Pyrolysis temperature is another key factor affecting the adsorption capacity of biochar. Increasing the pyrolysis temperature from 600°C to 1000°C leads to an increase in specific surface area and carbon content. Although increasing the surface area has a positive effect on the absorption of pollutants, increasing the carbon content means a decrease in functional groups, especially oxygen-containing groups, which has a negative impact on the adsorbent performance.
[0052] To further explore the effect of pyrolysis temperature on adsorption capacity, CLBC0.25-800 and CLBC0.25-1000 were synthesized at 800 °C and 1000 °C, respectively. Figure 2 b It can be seen that the TeA removal efficiencies of CLBC0.25, CLBC0.25-800 and CLBC0.25-1000 are 15.7%, 97.0% and 84.9%, respectively, among which the TeA removal efficiency of CLBC0.25-800 is about 6.2 times that of CLBC0.25, indicating that the pyrolysis temperature has a great influence on the adsorption capacity of biochar.
[0053] from Figure 4 It can be clearly seen that CLBC0.25, CLBC0.25-800 and CLBC0.25-1000 still maintain hollow tubular structures after calcium lactate modification and high-temperature calcination, which is consistent with the SEM results of corn straw biochar. The difference is that the surface of CLBC0.25 is smoother than that of CLBC0.25-800 and CLBC0.25-1000. In addition, when calcium lactate is used as a chemical activator, the interaction between calcium lactate and biomass at 1000°C will partially destroy the original pore structure and generate fewer oxygen-containing functional groups. Figure 2 As shown in Figure e, at the appropriate temperature, the surface of CLBC0.25-800 becomes rougher and the pore structure becomes richer due to the evaporation of volatile components and water. Calcium modification leads to the accumulation of sponge-like debris on the surface of biochar, forming more adsorption sites, which helps to improve the adsorption capacity.
[0054] The above discussion was further verified by characterizing the N2 adsorption–desorption isotherms, BJH desorption pore distributions, and XRD spectra of CLBC0.25, CLBC0.25-800, and CLBC0.25-1000, and the excellent adsorption capacity of CLBC0.25-800 for TeA was explored.
[0055] like Figure 2 As shown in g N2 adsorption-desorption isotherms, CLBC0.25, CLBC0.25-800 and CLBC0.25-1000 exhibit typical IV-type curves with H3-type hysteresis loops, indicating that the presence of mesoporous channels is conducive to the adsorption of TeA. The following results can be observed from the N2 adsorption-desorption isotherms of CLBC0.25-800: When the relative pressure (P / P0) is less than 0.1, nitrogen adsorption increases significantly, indicating the formation of micropores. There is no obvious saturated adsorption platform in the H3-type hysteresis loop, and the pore structure is irregular. When the relative pressure (P / P0) is between 0.4 and 1.0, obvious hysteresis occurs, indicating the generation of mesopores. Pore size distribution ( Figure 5 ) showed that the pore size distribution was mainly in the range of 3-40 nm. In addition, compared with CLBC0.25 and CLBC0.25-1000, CLBC0.25-800 had the largest specific surface area and total pore volume, which were 215.4440 m 2 g -1 and 0.150971 cm 3 g -1 The average pore size is medium, which is 2.8030 nm (Table 2), which is consistent with the SEM results. The above proves that the pore structure of CLBC0.25-800 is rich and irregular, and there is sponge-like debris accumulation on the surface of the hollow tubular structure. The pore volume and specific surface area are large, which is more conducive to TeA adsorption.
[0056] Table 1 Specific surface area (SSA), pore volume and pore size of corn straw biochar CLBC0.05, CLBC0.25, CLBC0.5, CLBC and CLBC2
[0057] Table 2 Specific surface area (SSA), pore volume and pore size of CLBC0.25, CLBC0.25-800 and CLBC0.25-1000
[0058] Study on the Adsorption Performance of CLBC.25-800 to TeA In order to optimize the CLBC0.25-800 dosage, the adsorption capacity and removal efficiency of TeA at different adsorbent dosages (0, 1, 3, 5, 10, 12, 20 g / L) were investigated as a function of adsorption time, and the adsorption capacity and removal efficiency were plotted. Figure 6 a and Figure 6 b. As the dosage of CLBC0.25-800 increased from 1 g / L to 3 g / L, the adsorption amount and removal rate of TeA increased significantly, indicating that the increase in the dosage of the adsorbent increased the adsorption sites of the adsorbent (oxygen-containing groups, calcium ions, aromatic rings, etc.). When the adsorbent dosage increased from 3 g / L to 10 g / L, the removal rate of TeA still increased, but the adsorption amount began to decrease. This is due to the decrease in the ratio of TeA molecules to adsorption sites, resulting in a decrease in unit adsorption capacity. Although the addition amount was further increased from 10 g / L to 20 g / L, the removal efficiency was only slightly improved. This may be because as the adsorption proceeded, the TeA concentration gradually decreased, the mass transfer resistance increased, and the adsorption performance was limited. Therefore, the optimal adsorbent dosage of 3 g / L was selected from an effective and economical perspective.
[0059] The effect of initial concentration on the adsorption capacity and removal efficiency of TeA was investigated. Figure 6 From the adsorption results of c, it can be seen that at a fixed dose of CLBC0.25-800, as the initial concentration of TeA increases from 10 μg / L to 400 μg / L, the adsorption capacity increases steadily, indicating that the higher the initial concentration, the more driving force there is to overcome the mass transfer resistance between the adsorbent and the solution. When the initial concentration increases from 10 μg / L to 50 μg / L, the removal efficiency increases, and when the initial concentration increases from 50 μg / L to 400 μg / L, the removal efficiency decreases slightly, and when the initial concentration is 400 μg / L, the removal efficiency decreases significantly. This is because the limited adsorption sites on the surface of the adsorbent are gradually completely occupied by TeA molecules, and too many TeA molecules lead to a decrease in removal efficiency. In order to maximize the effect of the adsorbent, 100 μg / L was selected as the initial TeA concentration.
[0060] This work also studied the effect of temperature on the adsorption capacity and removal efficiency of TeA by CLBC0.25-800. Figure 6 As shown in Figures 6e and 6f, within the temperature range of 30°C to 50°C, the adsorption capacity and removal efficiency of TeA decrease rapidly with the increase of temperature. Considering the negative effect of temperature increase on the adsorption capacity of TeA, this adsorption process is classified as an exothermic process. The exothermic adsorption process is mainly guided by physical adsorption, and the intermolecular force (van der Waals force) between the adsorbate and the adsorbate releases heat. As can be seen from the figure, 30°C is the optimal adsorption temperature.
[0061] Figure 6The curves of the effects of different adsorbent dosages, initial TeA concentrations and temperatures on the adsorption capacity and removal efficiency of CLBC0.25-800 adsorbing TeA over time are shown. Figure 6 It can be seen that within 40 min, as the adsorption process progressed, the adsorption capacity and removal efficiency increased rapidly, and the curves were basically constant at 60 min, so 60 min was selected as the optimal adsorption time.
[0062] Kinetic study of TeA adsorption The pseudo-first-order model, pseudo-second-order model, Elovich model and intra-particle diffusion kinetic model were used to study the adsorption kinetics of TeA. The kinetic fitting curve and parameter values of CLBC0.25-800 for TeA adsorption are shown in Figure 2. Figure 7 a and Table 3. The adsorption rate quickly tended to be constant within 60 min, indicating that TeA and CLBC0.25-800 completed the adsorption of binding sites in a relatively short time. This is because in the early stage of adsorption, a large number of TeA molecules in the solution bind to the abundant unoccupied adsorption sites on the surface of biochar. In the subsequent adsorption process, the adsorption sites on the surface of CLBC0.25-800 gradually became saturated, and the TeA molecules diffused into the adsorption particles to occupy the internal sites, so the adsorption equilibrium time was about 60 min. Although the pseudo-first-order model fits better than the pseudo-second-order model, the regression coefficient (R 2 ) is 0.999, and the regression coefficient of the quasi-second-order model (R 2 ) is 0.995, but the latter is also higher. It proves that physical adsorption is the rate-limiting step of the adsorption process, and chemical adsorption plays an auxiliary role. The above results confirm that CLBC0.25-800 has a large specific surface area and pore volume, which is conducive to accelerating physical diffusion. TeA can be converted into a stable metal salt (Ca(TeA)2) with calcium. The Ca of CLBC0.25-800 2+ The sites can bind to TeA to achieve selective chemical adsorption. The equilibrium adsorption capacity fitted by the pseudo-first-order kinetic model is 31.98 μg / g, which is consistent with the experimental data.
[0063] The intraparticle diffusion kinetic model was used to fit the experimental data to verify whether the rate-limiting step of TeA adsorption by CLBC0.25-800 is intraparticle diffusion. Figure 7 As shown in b, the adsorption curve is fitted for phase 1 and phase 2, R 2are 0.988 and 0.908 respectively. Stage 1 represents the surface diffusion of TeA on the adsorbent surface, and stage 2 represents the intra-mesoporous diffusion of TeA. The slope of stage 1 (k3-1) is 5.043, which is significantly greater than the slope of stage 2 (k3-2) (0.144), indicating that the diffusion rate of TeA on the adsorbent surface is greater than the diffusion rate inside the adsorbent. The intercepts c of the two phases are not zero, indicating that the intra-particle diffusion process is not the only rate-limiting step of adsorption, and surface adsorption has a greater contribution to the adsorption process. Other processes such as complexation also participate in the adsorption process.
[0064] Isothermal study of TeA adsorption The experimental data were linearly fitted using three adsorption isotherm models: Langmuir model, Freundlich model and Temkin model. The fitting curves are shown in Figure 2. Figure 7 c. The relevant parameters of the adsorption isotherm model were calculated and listed in Table 3. The results show that the R 2 The maximum adsorption of TeA (q m ) was 134.62 μg / g, and RL was 0.028 (between 0 and 1), indicating that the adsorption process was easy to occur.
[0065] Table 3 Adsorption isotherms and kinetic fitting parameters of CLBC0.25-800 for TeA
[0066] Thermodynamic study of TeA adsorption In order to further understand the adsorption mechanism of TeA on CLBC0.25-800, the adsorption experimental data at different temperatures were thermodynamically analyzed to obtain the optimal initial TeA concentration. As can be seen from Table 4, ΔG 0 It is negative at different temperatures, ranging from -20 to 0 kJ / mol, indicating that the adsorption of TeA by CLBC0.25-800 is a spontaneous physical adsorption process that does not require external energy. In addition, the ΔG° value decreases with increasing temperature, that is, the spontaneity of the adsorption of TeA by CLBC0.25-800 decreases with increasing temperature. ΔH° is negative, indicating that the adsorption of TeA by CLBC0.25-800 is an exothermic reaction, and increasing the temperature may slow down the reaction rate, which is consistent with Figure 6 e and Figure 6f. The negative value of ΔS indicates that the disorder degree of TeA decreases during the adsorption process on the CLBC0.25-800 surface.
[0067] Table 4 Thermodynamic parameters of TeA adsorption on CLBC0.25-800
[0068] Adsorption mechanism In order to intuitively explore the absorption mechanism of TeA, corn straw biochar, CLBC0.25 and CLBC0.25-800 were characterized. Figure 8 As shown in a, the XRD spectrum of CLBC0.25-1000 is as follows Fig. 9 shown.
[0069] Compared with corn straw biochar, the diffraction peaks of CLBC0.25 and CLBC0.25-800 changed significantly, and the peak intensity increased, indicating that the Ca ions on the modified biochar were chemically bonded, and the pyrolysis temperature had a great influence on the crystal structure. The diffraction peaks of CLBC0.25 at 23.0°, 29.4°, 35.9°, 39.5°, 43.2°, 47.4°, 48.5°, 57.3° and 60.8° mainly correspond to the (012), (104), (110), (113), (202), (018), (116) and (122) planes of CaCO3 (PDF 05-0586); the diffraction peaks of CLBC0.25-1000 at 18.0°, 28.6°, 47.1°, 50.8°, 54.3°, 62.6°, 64.2°, 71.7° and 84.6° mainly correspond to the (001), (100), (102), (110), (111), (201), (112), (202) and (211) planes of Ca(OH)2 (PDF 44-1481). Among them, the XRD diffraction peaks of CLBC0.25-800 obviously correspond to CaCO3 (PDF 05-0586) and Ca(OH)2 (PDF 44-1481). It can be seen that in the process of synthesizing CLBC, CaCO3 is mainly generated at 600℃, while Ca(OH)2 is mainly generated at 1000℃. When the pyrolysis temperature is 800℃, part of CaCO3 decomposes and reacts with water vapor to generate Ca(OH)2, resulting in the coexistence of CaCO3 and Ca(OH)2. Combined with the maximum TeA removal efficiency CLBC0.25-800, it is proved that the pyrolysis temperature of 800℃ is not only conducive to the formation of adsorbent materials with large specific surface area, but also the coexistence of CaCO3 and Ca(OH)2 is more conducive to the selective adsorption of TeA. This may be due to (i) Ca(OH)2 is easier to release Ca than CaCO3 2+ and coupled with TeA to form a complex; (ii) when CaCO3 and Ca(OH)2 coexist, it is easier to form a porous structure with a larger specific surface area.
[0070] Figure 8 b is the FTIR spectra of corn straw biochar CLBC0.25 and CLBC0.25-800. Corn straw biochar has a wavelength of 3437.9 cm -1 The fluctuation band at 2924 cm-1 belongs to -OH. After CLBC0.25 and CLBC0.25-800 reacted with calcium lactate at 600℃ and 800℃, the peak intensity of -OH group gradually increased. This may be due to the fact that more Ca(OH)2 will be produced at higher reaction temperature. -1 and 1457.7 cm -1The stretching vibration bands loaded at 1631.7 cm -1 The C=C band at the 400 nm corresponds to conjugated olefins, such as aromatic rings. The C=C group peak intensity of CLBC0.25-800 is the largest, indicating that its chemical structure is more stable and its π-π interaction with TeA is stronger than that of corn straw biochar and CLBC0.25.
[0071] The XPS spectra of C 1s, N 1s, and O 1s of corn straw biochar, CLBC0.25, and CLBC0.25-800 are shown in Figure 2. Figure 8 c. After activation with calcium lactate, characteristic peaks of Ca 2p appeared in CLBC0.25 and CLBC0.25-800, further proving the successful introduction of Ca. The high-resolution spectra of C 1s, O1s and Ca 2p of CLBC0.25-800 are shown in Figure 8 shown. Figure 8 The C1s spectrum shown in d can be deconvoluted into CC or C=C with a binding energy of 284.8 eV, CO or CN with a binding energy of 285.6 eV, OC=O with a binding energy of 289.6 eV, and π-π* with a binding energy of 293.5 eV. The oxygen-containing functional groups on the biochar surface can provide potential active sites for the absorption of TeA. Figure 8 From the high-resolution spectrum of O 1s of e, the peak at 531.4 eV binding energy belongs to CO, and the peak at 532.3 eV is attributed to CO3 2- match. Figure 8 The Ca 2p spectrum in f shows two peaks, Ca 2p3 / 2 and Ca 2p1 / 2, at 350.7 eV and 347.2 eV, respectively, confirming the presence of Ca. Combining the high-resolution spectra of O1s and Ca 2p, the formation of CaCO3 can be confirmed.
[0072] Adsorption of TeA in apple juice by CLBC0.25-800 To evaluate the adsorption effect of CLBC0.25-800 on TeA in real samples, three experimental groups were conducted under the optimal adsorption conditions (temperature = 30 °C, adsorption time = 100 min): (A) clean apple juice; (B) apple juice with 100 μg / L TeA added; (C) 3 g / L CLBC0.25-800 added to apple juice containing 100 μg / L TeA. 20% water was added to the apple juice during the extraction process.
[0073] At present, there are few adsorbents for TeA adsorption, and most of them are bio-adsorption inactivated cells as adsorbents, which are relatively expensive. According to existing reports, different adsorbents for TeA adsorption have been found, and their adsorption capacities are listed in Table 5. The adsorption capacities of CLBC0.25-800 for TeA in apple juice and aqueous solution are 7.18 μg / g and 31.98 μg / g, respectively, which are higher than the adsorption capacities of other adsorbents for fruit juice and aqueous solution, proving that CLBC0.25-800 does have an excellent adsorption effect. The adsorption capacity of CLBC0.25-800 for TeA in spiked apple juice is significantly lower than that in TeA aqueous solution. This may be due to the viscous texture of the solution caused by the sugar molecules in apple juice, the increased mass transfer resistance, and the inability of the adsorbents to fully contact with each other, thereby reducing the adsorption capacity. The Chinese national standard methods of GB 5009.8-2023 and GB 5009.157-2016 were used to analyze the contents of sugar (fructose, glucose, sucrose, μg / 100g) and malic acid (μg / kg) in groups A, B, and C. The experimental results ( Fig.10 ) showed that the adsorption did not significantly change the quality of apple juice.
[0074] Table 5 Comparison of the adsorption performance of different adsorbents on TeA
[0075] The above is only a specific implementation of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for preparing calcium lactate modified corn straw biochar, characterized in that: The following steps are involved: The first step is the preparation of biomass powder, which includes washing, drying, crushing and sieving the corn straw to obtain uniform corn straw biomass powder; the second step is the preparation of calcium lactate modified corn straw biochar, which includes uniformly mixing the obtained corn straw biomass powder and calcium lactate according to a proportion, then fully grinding and placing them in a tubular furnace for reaction to obtain calcium lactate modified corn straw biochar.
2. The method for preparing calcium lactate modified corn straw biochar according to claim 1, characterized in that: In the step 1, the corn stalks are cleaned and cut into 10 cm segments, dried at 105° C. overnight, and crushed and passed through a 60-mesh sieve.
3. The method for preparing calcium lactate modified corn straw biochar according to claim 1, characterized in that: The ratio of calcium lactate to corn straw powder is 1:20, 1:4, 1:2, 1:1 or 2:
1.
4. The method for preparing calcium lactate modified corn straw biochar according to claim 3, characterized in that: In the step 2, the tubular furnace is filled with N2 gas, heated to 600-1000°C at a heating rate of 5°C / min, and maintained at 600-1000°C for 1 h, and finally cooled to room temperature, the prepared biochar is taken out, washed twice with distilled water, and placed in a 105°C oven for 12 h to obtain calcium lactate modified corn straw biochar.
5. The method for preparing calcium lactate modified corn straw biochar according to claim 4, characterized in that: The tube furnace was filled with N2 gas and heated to 800°C at a heating rate of 5°C / min and maintained at 800°C for 1 h.
6. Effect of the calcium lactate-modified corn straw biochar prepared by the method for preparing calcium lactate-modified corn straw biochar according to any one of claims 1 to 5 in the adsorption of TeA.